The crystal structure of 1,1′-(2,3,5,6-tetramethylpyrazine-1,4-diyl)bis(ethan-1-one), C12H18N2O2 - Wang Yuwen; Cui Ruolin; Zhang Chunteng (Zeitschrift für Kristallographie - New Crystal Structures)
C12H18N2O2, monoclinic, P21/n (no. 14), a = 9.2113(4) Å, b = 11.9224(6) Å, c = 11.4469(4) Å, β = 96.413(2)°, V = 1249.24(9) Å3, Z = 4, Rgt(F) = 0.0589, wRref(F2) = 0.1869, T = 655 K.